Soy isoflavone reduces LPS-induced acute lung injury via increasing aquaporin 1 and aquaporin 5 in rats - Wang, Xiaobo; Zhang, Yili; Zhou, Xiuyun; Xia, Xiumei; Teng, Weijun; Sheng, Lin; Ding, Jing (Open life sciences, 2023)
Acute lung injury (ALI) followed with severe inflammation and oxidative stress. Anti-inflammatory and antioxidant are the properties of aquaporin 1 (AQP1) and aquaporin 5 (AQP5). The goal of this study was to see if soy isoflavone can diminish lipopolysaccharide (LPS)-induced ALI and the underling mechanism. LPS-induced ALI was given to Sprague–Dawley rats 14 days following oophorectomy. One hour before the LPS challenge, estradiol (1 mg/kg) was administered subcutaneously as positive control and soy isoflavone was intragastric administration for 14 days prior to LPS challenge with different doses. Six hours after LPS challenge, the pulmonary edema, pathophysiology, inflammation, and the oxidative stress in lung tissues of rats were discovered. We found that soy isoflavone can reduce pulmonary edema and the lung pathology in a dose-dependent manner. Furthermore, tumor necrosis factor-alpha, interleukin-1β, and interleukin-6 were decreased in rats treated with soy isoflavone. Meanwhile, soy isoflavone reduced pulmonary oxidative stress by decreasing malondialdehyde levels, while increasing superoxide dismutase levels in lung tissues in a dose-dependent manner. Mechanically, we found that the mRNA and protein level of AQP1 and AOP5 were increased in lung tissues of rats treated with soy isoflavone compared the LPS-treated rats. Thus, soy isoflavone alleviates LPS-induced ALI through inducing AQP1 and AQP5.